Theaters of justice : judging, staging, and working through in Arendt, Brecht, and Delbo - Horsman, Yasco (Cultural memory in the present., 2011)
What role do legal trials have in collective processes of coming to terms with a history of mass violence? How does the theatrical structure of a criminal trial facilitate and limit national processes of healing and learning from the past? This study begins with the widely publicized, historic trials of three Nazi war criminals, Eichmann, Barbie, and Priebke, whose explicit goal was not only to punish, but also to establish an officially sanctioned version of the past. The Truth and Reconciliation commissions in South America and South Africa added a therapeutic goal, acting on the belief that.